The costs of VAT: A review of the literature - Luca Barbone; Richard M. Bird; Jaime Vázquez Caro (Center for Social and Economic Research (CASE), 2012)
This paper reviews the published literature on the definition and measurement of the administrative and compliance costs of taxation, with special reference to VAT (including evasion and fraud) in the European Union.
Keywords: H20; H21; H25; H26; M48; 330; Taxation; Subsidies; Revenue; Steuer; Umsatzsteuer; Folgekosten; Steuerstrafrecht; Steuervermeidung; Bibliometrie; EU-Staaten